AKTIVITAS IMUNOMODULATOR FRAKSI ETIL ASETAT DAUN SOM JAWA (Talinum paniculatum (Jacq.) Gaertn) TERHADAP RESPON IMUN SPESIFIK - Ika Puspitaningrum; Yuvianti Dwi Franyoto; Siti Munisih (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2018)
ABSTRACTEthyl acetate fraction of Som Java leaves (Talinum paniculatum (Jacq.) Gaertn) has been shown to boost innate immunity in the body (non-specific immunomodulatory activity). This study aims to determine the immunomodulatory activity of the specific response of the ethyl acetate fraction of Som Java leaves (Talinum paniculatum (Jacq.) Gaertn). Test specific immune response by using delayed type hypersensitivity test and total antibody titers test. Analysis of data obtained using SPSS version 16.0. Delayed type hypersensitivity test results showed that the ethyl acetate fraction Som Java leaves 50, 100 and 150 mg/kgbw proven to increase cellular immune response and activities comparable to the positive control. Total antibody titer test results showed that the fraction of ethyl acetate Som Java leaves three doses shown to increase the value of primary and secondary antibody titers. Based on the test results specific response can be concluded that the ethyl acetate fraction Som Java leaves have specific immunomodulatory activity.Keywords: Talinum paniculatum (Jacq.) Gaertn, immunomodulatory, delayed type hypersensitivity, total antibody titer test